1986
DOI: 10.1002/jor.1100040404
|View full text |Cite
|
Sign up to set email alerts
|

Joint reaction to polyethylene implantation: A method for inducing osteoarthritic change and osteophyte formation in the rabbit knee joint

Abstract: Joint lesions were induced by implantation of a rigid piece of polyethylene sutured under the patella and quadriceps tendon of the rabbit's right knee. Compared to the left sham-operated knee, follow-up studies revealed progressive changes that consisted of early and transient synovial hyperemia and proliferation and late osteoarthritis. By day 7 after surgery, soft synovial-like tissue proliferated around the implant and the articular margins of the femoral trochlea indicating primitive "osteophytic" protuber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Recent studies suggest that wear debris may play a fundamental role in a cascade of events with consequent osteolysis and bone resorption. [1][2][3][4][5] It has been reported that retrieved periprosthetic tissues contain significant volumes of submicron-sized, ultrahigh molecular weight polyethylene (UHMWPE) particles. [6][7][8][9][10] This is consistent with an emerging view that polymer wear debris, particularly ultra-high molecular weight polyethylene, plays an important role in the development of osteolysis and premature device failure.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest that wear debris may play a fundamental role in a cascade of events with consequent osteolysis and bone resorption. [1][2][3][4][5] It has been reported that retrieved periprosthetic tissues contain significant volumes of submicron-sized, ultrahigh molecular weight polyethylene (UHMWPE) particles. [6][7][8][9][10] This is consistent with an emerging view that polymer wear debris, particularly ultra-high molecular weight polyethylene, plays an important role in the development of osteolysis and premature device failure.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest that wear debris may play a fundamental role in a cascade of events with consequent osteolysis and bone resorption. [1][2][3][4][5] It has been reported that retrieved periprosthetic tissues contain significant volumes of submicron-sized, ultrahigh molecular weight polyethylene (UHMWPE) particles. [6][7][8][9][10] This is consistent with an emerging view that polymer wear debris, particularly ultra-high molecular weight polyethylene, plays an important role in the development of osteolysis and premature device failure.…”
Section: Introductionmentioning
confidence: 99%